Perbandingan Peribahasa Jepang dengan Peribahasa Sunda terkait Hubungan Manusia: Kajian Semantik Kognitif - Puspa Mirani Kadir; Yulia Pebriani; Susiyanti Rusyan (JENTERA: Jurnal Kajian Sastra, 2022)
Proverbs are a local wisdom or folksy wisdom that contains morals or truths that are values embraced by a society. This is in accordance with Foley (1997, 361) who states that proverbs are a remarkable example of describing the relationship between culture, language, and the human mind. This simple contrast research of the analysis will adjust to important variables in the content analysis. The first time that is done is to analyze proverbial data in two languages, namely Sundanese and Japanese, meaning the same based on a cultural point of view to which four content variables will be analyzed. These four variables are the concept of Warnaen, (1987, 5) in facilitating the grouping of proverbial contents. After that, it is continued with an analysis scheme that refers to the prism model developed by Geeraerts in Langlotz's book entitled Idiomatic Creativity. The model illustrates the existence of a metaphorical relationship between the true meaning of a proverb and the language used in the idiom (Langlotz, 2006, 109). Sundanese and Japanese proverbs in the variable content category are closely related to humans as individuals and humans in social life. In addition, Sundanese proverbs found in oral tradition have a deep meaning in a process of human behavior that behaves, while the dominant Japanese proverb tells of a human behavior from the beginning of the event then continued with a result accompanied by a causal relationship. AbstrakPeribahasa merupakan suatu kearifan lokal atau folksy wisdom yang mengandung moral atau kebenaran yang menjadi nilai yang dianut oleh suatu masyarakat. Hal ini sesuai dengan Foley (1997, 361) yang menyatakan bahwa peribahasa (proverb) merupakan contoh yang luar biasa untuk menggambarkan hubungan antara budaya, bahasa, dan pikiran manusia. Penelitian kontrastif analisis yang sederhana ini akan menyesuaikan dengan variabel penting dalam analisis isi. Pertama kali yang dilakukan adalah menganalisis data peribahasa dalam dua bahasa, yaitu Sunda dan Jepang, bermakna sama berdasarkan sudut pandang budaya yang akan dianalisis empat kategori isi. Empat kategori ini merupakan konsep dari Warnaen, (1987, 5) dalam memudahkan pengelompokan isi peribahasa. Setelah itu dilanjutkan dengan skema analisis yang mengacu pada model prisma yang dikembangkan oleh Geeraerts dalam buku Langlotz yang berjudul Idiomatic Creativity. Model tersebut menggambarkan akan adanya hubungan metafora antara makna sesungguhnya suatu peribahasa dengan bahasa yang digunakan dalam idiom tersebut (Langlotz, 2006, 109). Peribahasa Sunda dan Jepang dalam kategori variabel isi sangat berkaitan erat dengan manusia sebagai pribadi dan manusia dalam kehidupan bermasyarakat. Selain itu, peribahasa Sunda yang ditemukan dalam tradisi lisan memiliki makna yang dalam pada suatu proses manusia itu berperilaku, sedangkan peribahasa Jepang dominan menceritakan sebuah perilaku manusia dari awal kejadian kemudian dilanjutkan dengan hasil yang disertai dengan hubungan sebab akibatnya.